Coping Stres pada Anggota Kepolisian Bagian Dalmas (Pengendalian Massa) di Polres Sukoharjo - Desy Rosiana; Dhian Riskiana Putri; Faqih Purnomosidi (Pusat Riset dan Inovasi Nasional, 2025)
Work stress is a major challenge faced by police officers, especially in the Dalmas (Crowd Control) unit that is directly involved in handling crowd and high-risk situations. This study aims to describe the forms of stress coping used by Dalmas Polres Sukoharjo members and the factors that influence it. The method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation of seven selected informants. The results of the study indicate that the majority of Dalmas members tend to use emotion-focused coping strategies, such as listening to music, playing games, karaoke, fishing, and family time to relieve psychological stress. On the other hand, problem-focused coping was also found, although not dominant, in the form of seeking social support, planned problem solving, and calming instrumental activities. These findings indicate that emotional coping strategies are the main choice in dealing with work stress in the Dalmas Polres Sukoharjo unit, but the development of active problem-solving-based coping strategies is still needed to support long-term mental resilience. This study is expected to be the basis for formulating institutional psychological support policies for police officers in high-risk work environments.